2014
DOI: 10.14202/vetworld.2014.807-810
|View full text |Cite
|
Sign up to set email alerts
|

Association study of genetic variants at single nucleotide polymorphism rs109231409 of mannose-binding lectins 1 gene with mastitis susceptibility in Vrindavani crossbred cattle

Abstract: Aim: The present study was undertaken to identify whether single nucleotide polymorphism (SNP) rs109231409 located on mannose-binding lectins 1 (MBL1) gene was associated with mastitis tolerance/susceptibility. Materials and Methods:After grouping 100 Vrindavani crossbred cattle as mastitis positive and negative animals, they were genotyped using polymerase chain reaction (PCR)-restriction fragment length polymorphisms method. Gene and genotype frequencies of different patterns were estimated by standard proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…The results from this study differs with the earlier reports of Wang et al [6]; Liu et al [9]; Yuan et al (2013) and Asaf et al [10,11].These differences might be due to differences in target region of the gene, genetic variation between the species and can also be due to small population size in the present study . However, the SNPs and haplotypes described in our study were novel and have not been reported till date.…”
Section: Ethical Approvalcontrasting
confidence: 99%
See 1 more Smart Citation
“…The results from this study differs with the earlier reports of Wang et al [6]; Liu et al [9]; Yuan et al (2013) and Asaf et al [10,11].These differences might be due to differences in target region of the gene, genetic variation between the species and can also be due to small population size in the present study . However, the SNPs and haplotypes described in our study were novel and have not been reported till date.…”
Section: Ethical Approvalcontrasting
confidence: 99%
“…In Chinese Holstein cattle, a total of 5 SNPs have been reported for MBL1 gene, and the combined genotype ATGGC/ACAAC exhibited the lowest, thus MBL1 gene possibly contributes to bacterial infection resistance and was proposed as a molecular marker of milk production traits to control mastitis [9]. In Vrindavani crossbred cattle, SNPs have been reported to be polymorphic in both the affected as well as unaffected groups of cows but no significant association has been found with the clinical mastitis [10,11]. Three SNPs at (c.1252G>A in intron1, c.2534G>A and c.2569T>C in exon2) have been reported in MBL1 gene.…”
Section: Introductionmentioning
confidence: 99%
“…Asaf et al . [ 56 ] in their work on MBL-1 (Chromosome 28) with PCR-RFLP claimed no significant association between SNP “rs109231409” with mastitis tolerance or susceptibility in Vrindavani crossbred cattle. Further, Zhao et al .…”
Section: Immuno-pathogenesismentioning
confidence: 99%
“…However, AACCEE genotype associated with the lowest SCS was favorable for the mastitis resistance. Asaf et al 2014 reported that single nucleotide polymorphism rs109231409 located on mannose-binding lectins 1 (MBL1) gene was not associated with mastitis tolerance/susceptibility. , reported polymorphism of the BRCA1 SNPs, i.e., G22231T but reported no significant association with mastitis susceptibility in Vrindavani cattle by PCR-RFLP.…”
Section: Mastitismentioning
confidence: 99%